Straying From the Righteous Path and From Ourselves: The Interplay Between Perceptions of Morality and Self-Knowledge. (November 2016) - Christy, Andrew G.; Seto, Elizabeth; Schlegel, Rebecca J.; Vess, Matthew; Hicks, Joshua A.
The present research addresses the relationship between morally valenced behavior and perceptions of self-knowledge, an outcome that has received little attention in moral psychology. We propose that morally valenced behavior is related to subjective perceptions of self-knowledge, such that people experience lower levels of self-knowledge when they are reminded of their immoral behaviors. We tested this proposition in four studies ( N = 1, 177). Study 1 used daily-diary methods and indicates that daily perceptions of self-knowledge covary with daily levels of morally valenced behavior. The final three studies made use of experimental methods and demonstrate that thinking about immoral behaviors attenuates current perceptions of self-knowledge. The predicted relationships and effects generally persist when controlling for self-esteem. Based on our findings, we argue that perceived self-knowledge may play a functional role in moral self-concept maintenance and moral regulatory processes.